IMPLICATIONS OF AUTOGATE AS THE OPTIMIZATION OF IMMIGRATION TECHNOLOGY IN RELATIONSHIP TO REDUCE THE CRIMINAL ACTION OF HUMAN TRAFFICKING - Atsil Syah Gibran; Sekar Arini Prakita; Muhammad Choirul Yusuf; Sarina Riyadi (Polteknik Imigrasi, 2023)
Human Trafficking is an extraordinary crime because it is generally involved with sexual offenses and forced labour; which is a clear violation of human rights. Autogate technology has been implemented at Soekarno-Hatta Airport to speed up departure and arrival procedures at the country's entrance; however, it is seen as a potential risk factor for trafficking. While technologies such as biometric scanning and automated processing speed up document checks for immigration with Autogate, fewer opportunities for people to interact directly with security agents increase the risk of trafficking. Some analyzes must consider many variables, such as the security of autogate technology, the expansion of human movement, and the protection of human rights. This essay aims to attenuate how implementing autogate can impact human trafficking. Moreover, with the existence of an autogate, these findings will help policy makers develop more effective steps to prevent human trafficking.